2021
DOI: 10.3390/w13182559
|View full text |Cite
|
Sign up to set email alerts
|

Application of Tea Polyphenols and Their Effects on Ultrafiltration Effluent Disinfection and Microbial Risk

Abstract: To reduce the risk of by-products from traditional disinfection technology and to ensure safe water quality, tea polyphenols (TP) were used as disinfectants after the ultrafiltration (UF) process. The disinfectant effect of TP was tested on the total number of bacteria and changes in bacterial community structure, and pathogen virulence factors were detected by Illumina’s high-throughput sequencing technology. The results showed that the recommended dosage of TP for water treatment after UF was 5 mg/L, which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…This indicates that the long-lasting tea polyphenol disinfecting property is more pronounced for the ozone-tea polyphenol disinfection strategy. Feng et al (2021b) found that the decay characteristics of tea polyphenols when used as the only disinfectant together with ultrafiltrated effluent fit the second-order kinetics equation. The attenuation of tea polyphenols was greatly affected by the initial concentration and reaction temperature.…”
Section: Chemical and Biological Stabilitymentioning
confidence: 91%
See 1 more Smart Citation
“…This indicates that the long-lasting tea polyphenol disinfecting property is more pronounced for the ozone-tea polyphenol disinfection strategy. Feng et al (2021b) found that the decay characteristics of tea polyphenols when used as the only disinfectant together with ultrafiltrated effluent fit the second-order kinetics equation. The attenuation of tea polyphenols was greatly affected by the initial concentration and reaction temperature.…”
Section: Chemical and Biological Stabilitymentioning
confidence: 91%
“…This indicates that tea polyphenols are advantageous in inhibiting chlorine-resistant bacteria and pathogenic bacteria. Feng et al (2021b) used the BLAST similarity comparison search method to establish the MvirDB protein database. Their analysis found that the types of water-based toxicity factors decreased by 56 following tea polyphenol treatment, and the total absolute abundance decreased by 51%.…”
Section: As the Main Disinfectant Of Uf Effluentmentioning
confidence: 99%